Effects of Acute and Chronic Exercise on Immunological Parameters in the Elderly Aged: Can Physical Activity Counteract the Effects of Aging? - Sellami, Maha; Gasmi, Maha; Denham, Joshua; Hayes, Lawrence D.; Stratton, Dan; Padulo, Johnny; Bragazzi, Nicola (Frontiers in Immunology, 2018)
Immunosenescence is characterized by deterioration of the immune system caused by aging which induces changes to innate and adaptive immunity. Immunosenescence affects function and phenotype of immune cells, such as expression and function of receptors for immune cells which contributes to loss of immune function (chemotaxis, intracellular killing). Moreover, these alterations decrease the response to pathogens, which leads to several age-related diseases including cardiovascular disease, Alzheimer's disease, and diabetes in older individuals. Furthermore, increased risk of autoimmune disease and chronic infection is increased with an aging immune system, which is characterized by a pro-inflammatory environment, ultimately leading to accelerated biological aging. During the last century, sedentarism rose dramatically, with a concomitant increase in certain type of cancers (such as breast cancer, colon, or prostate cancer), and autoimmune disease. Numerous studies on physical activity and immunity, with focus on special populations (i.e., people with diabetes, HIV patients) demonstrate that chronic exercise enhances immunity. However, the majority of previous work has focused on either a pathological population or healthy young adults whilst research in elderly populations is scarce. Research conducted to date has primarily focused on aerobic and resistance exercise training and its effect on immunity. This review focuses on the potential for exercise training to affect the aging immune system. The concept is that some lifestyle strategies such as high-intensity exercise training may prevent disease through the attenuation of immunosenescence. In this context, we take a top-down approach and review the effect of exercise and training on immunological parameters in elderly at rest and during exercise in humans, and how they respond to different modes of training. We highlight the impact of these different exercise modes on immunological parameters, such as cytokine and lymphocyte concentration in elderly individuals.